A Critical Reading and an Experimental Mapping Proposal on the Concept of Personal Reach - Guney, Efsun Ekenyazici; Gorgulu, Tlin (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
The personal boundaries that an individual experiences can be figured out based on the relationship between dwelling, working and socializing as the three main axes of everyday life. The boundaries that are illustrated as the concept personal reach in this study, are being formulated in the influence of several parameters such as urbanization, transportation and housing. Focusing on transportation as one of the most distinctive parameters, the transformation of the transportation systems and vehicles in time are being investigated through the case study of Istanbul in the scope of this research. According to this context the transformative effects of transportation on the concept is being explored and the change of an individual's personal reach patterns are surveyed. In order to clarify the alternation mentioned, urban scale maps explaining the progress of the transportation systems are prepared to convey this progress visually. In the process of Istanbul's urbanization in time, early years of the republican era emerge as a distinguishing period in that transportation and the city co-evolve together. Accordingly, focusing on the first years of the republican era and the present days of Istanbul in particular, the survey presents a reading on the two eras' transportation opportunities regarding the personal reach concept through the maps configurated.
Keywords: Istanbul; transportation; personal reach; Architecture